Energy dependence of a scintillating fiber detector for preclinical dosimetry with an image guided micro-irradiator. (29th May 2019) - Le Deroff, C; Frelin, A-M; Ledoux, X
Abstract: The dosimetry of preclinical micro-irradiators is challenging due to their millimetric beams and medium x-ray energy range. Plastic scintillator dosimeters (PSD) are good candidates for such a purpose as they provide a high spatial resolution although they show an energy dependence below 100 keV. The purpose of this study was to assess the energy dependence of a dedicated PSD (called DosiRat) for micro-irradiators dosimetry. The response of the PSD relative to air kerma was measured for different beam qualities (40–225 kV) with the X-RAD 225Cx irradiator. The corresponding energy spectra, determined by Monte Carlo simulations, allowed for correcting the differences in absorbed dose between the DosiRat material (polystyrene) and the air and therefore allowed to compare DosiRat intrinsic energy response to the Birks scintillation quenching model. The energy response of DosiRat was then assessed under preclinical conditions through percentage depth dose curves (PDD) and relative output factor (ROF) measurements in water for beam diameters ranging from 1 to 25 mm. DosiRat energy response showed a coefficient of variation of 23% from 40 to 225 kV, mainly explained by the mass energy-absorption coefficient variation between polystyrene and air. A remaining variation was shown to be caused by the quenching of the scintillation and was correctly reproduced by the Birks model (with kB = 10.27 mg MeV −1 cm −2 ). PDD and ROF measurements highlighted an energy response variation with depth and collimation up to 10%. A dose accuracy better than 1% was finally achieved with appropriate calibration and correction factors (CF), for beam collimations larger than the detector ( 2 mm diameter). DosiRat energy dependence was fully characterized in preclinical energy range and shown to be negligible with convenient calibration and corrections factors. It provided accurate dosimetry for medium energy (225 kV) and millimetric beams (down to 2.5 mm).